The impact of plant-associated rhizobacteria on germination capacity, growth and productivity of spring field mustard and emmer wheat. Issue 1 (1st June 2022) - Lebedev, V; Kondrat, S; Uraev, G; Khuaz, S; Datkhuzheva, R
Abstract: The paper reports the results of field experiments that analysed changes in germination capacity, growth indicators and productivity of two crops in response to seed inoculation: field mustard ( Brassica campestris L.) of the Vostochnaya variety (k-274) and emmer wheat ( Triticum dicoccum subsp. asiaticum Vavilov) of k-7516 variety. Morphometric parameters and productivity of dry mass were measured during the major stages of crop development. The seeds of field mustard were inoculated with the following bacterial products: Mizorin ( Arthrobacter mysorens, strain 7), Mobilin ( Pseudomonas fluorescens, strain PG-5) and Flavobakterin ( Flavobacterium sp., strain 30). The seeds of emmer wheat were inoculated with Psevdomonas ( Pseudomonas fluorescens, strain PG-5) and Rizoagrin ( Agrobacterium radiobacter, strain 204). In addition, we also tested biinoculation (combined use of two bacterial products) for each crop. The study aimed to analyse changes in growth indicators and productivity of field mustard and emmer wheat in response to mono- and biinoculation of seeds with plant-associated rhizobacteria. The experiments showed that the application of bacterial products and increasing doses of mineral nitrogen has a stimulating effect on plants. The study proved monoinoculation to be more effective than biinoculation. This may be due to the competing effect of rhizobacterial strains from different bacterial products once the biinoculated seeds are put in soil.